PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO MITRA DATA DI BUMI SERPONG DAMAI (BSD) - Mawarni Dawolo; Irmal Irmal (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of Brand Image (X₁) and Product Quality (X₂) on Purchase Decision (Y) at Mitra Data Store in Bumi Serpong Damai (BSD). The method used in this study is a quantitative method with an associative approach. The sampling technique applied is probability sampling with the simple random sampling method, and the sample size is determined using the Slovin formula. The data analysis techniques used include regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicate that Brand Image (X₁) and Product Quality (X₂) have a significant effect on Purchase Decision (Y), with the regression equation Y = 8.091 + 0.662X₁ + 0.140X₂. The correlation coefficient shows a strong relationship with a value of 0.775. The coefficient of determination simultaneously influences the dependent variable by 0.601 or 60.1%. The simultaneous hypothesis test of Brand Image (X₁) and Product Quality (X₂) on Purchase Decision (Y) yields Fcount > Ftable (57.893 > 3.120); therefore, H₀ is rejected and H₃ is accepted. This indicates that Brand Image (X₁) and Product Quality (X₂) simultaneously affect Purchase Decision (Y).